PHYSICO-CHEMICAL CHARACTERIZATION OF UVARIA CHAMAE OIL AND QUALITY ASSESSMENT OF BIODIESEL PRODUCED FROM Uvaria chamae - Sani, A.; Uba, S.; Omoniyi, K. I.; Mikail, A. H. (FUDMA Journal of Sciences, 2023)
This research studied the potential of the seed oil of Uvaria chamae for biodiesel production. The oil was extracted using a soxhlet extractor and n-hexane as a solvent before being transesterified into biodiesel. The results obtained showed a low yield of 12.5 % for the extracted oil. The oil showed a high acid value of 14.02± 0.09 mgKOH/g, which indicated high free fatty acid content and the percentage yield of the biodiesel produced was 88.35± 0.5%. The profile of methyl esters showed that unsaturated linoleic methyl ester was dominant. The results suggested that Uvaria chamae seed oil possesses some properties that were suitable for biodiesel production.